The prevelance of psychosis in indigenous populations in Australia: A review of the literature using systematic methods. (June 2023) - Jewell, James; Mitchell, David
Objectives: To understand the prevalence of psychosis in Aboriginal and Torres Strait Islander populations. Methods: A systematic review of the literature was conducted using PubMed, Embase and Cochrane. Results: Eight studies were reviewed. The prevalence of psychosis appeared higher in Aboriginal and Torres Strait Islanders, compared with non-Aboriginal and Torres Strait Islander populations. Conclusion: Although the literature suggests the prevalence of psychosis in Aboriginal and Torres Strait Islander populations is substantial, there are few studies and limited scope. Cultural competency is essential to understanding psychosis in this context.